Perception of the Mosque Jama'ah Regarding the Leadership of the Chairman of DKM in Improving the Function of the Al-Jazeera Mosque - Tri Yugo Yugo (Jurnal Al-Hikmah, 2024)
This study evaluates the influence of the leadership of the Chairman of the Mosque Prosperity Council (DKM) and the quality of service on the perception of worshippers at the Al-Jazeera Mosque. Although the role of DKM leadership is important in improving the quality of mosque services, most previous studies have only emphasized the physical aspects and programmatic activities of mosques, thus paying less attention to how DKM leadership quality affects the perception of worshippers. This condition shows the need for a deeper understanding of the direct and indirect influence of leadership on the perception of worshippers, especially in the context of the management of mosques as spiritual and social centers. This study used a quantitative method with data collected through a Likert scale questionnaire to 33 respondents selected through purposive sampling. The validity and reliability test of the instrument was carried out using SPSS, also with a multicollinearity test and a heteroscedasticity test as a condition for the path analysis test. Meanwhile, the analysis of the relationship between variables was tested by path analysis using LISREL to examine direct and indirect influences. The results of the study show that the leadership of the Chairman of DKM and the quality of service have a significant influence on the positive perception of worshippers, which emphasizes the importance of leadership quality in optimizing the social and religious functions of mosques.